Selective enforcement and international criminal law : The International Criminal Court and Africa / James Nyawo. - Nyawo, James (Series Supranational criminal law ;, 2017)
The dynamics of enforcing international criminal justice through the International Criminal Court (ICC) has become a challenging exercise in Africa. At times the uneasy relationship between the ICC, the African Union and a few influential African states has given rise to concerns about the future of international criminal justice in general, and in Africa in particular. Still, the enthusiasts for international criminal justice as enforced by the ICC, interpret the challenges that the ICC is encountering in Africa as part of the growing pains of a new institution in the international system. The distractors have already prepared the ICC's obituary. One of the criticisms levelled against the ICC, and which is the motivation for, and central theme behind, this book is that it has morphed and ceased to be an independent legal institution instead becoming a political tool utilised by politically powerful states in the West against their political opponents in Africa. More specifically the Court is alleged to be selectively enforcing international criminal law by merely officially opening investigations and prosecutions in Africa. Although this book recognises that selective implementation of criminal justice is acceptable both at the domestic and international level, it analyses the legal and political factors behind the Court's focus on international crimes committed in Africa when there are other situations to which the court should potentially turn its attention, such as in Syria, Afghanistan or the Occupied Palestinian Territories. The book seeks to determine whether such a focus implies that Africa has the monopoly over international crimes or whether African victims or perpetrators are any different from those in the Middle East? In addition the book attempts to uncover the basis and the validity of the African Union and some African states' criticisms of the ICC. James Nyawo holds a Doctorate from the School of Law at Middlesex University, UK. He previously held the position of Visiting Lecturer with the Department of International & Cooperative Law at Khartoum University, Sudan and is currently an External Research Fellow at the International Victimology Institute (INTERVICT), Tilburg, Netherlands. He has worked as a humanitarian practitioner and consultant with national, international and UN agencies working with landmine victims, internally displaced persons and refugees in Angola, Uganda (North), South Sudan and Sudan.